Open Universities 2.0: Leadership, Strategic Reset and the National Agenda - Olcott, Don (Médiations & médiatisations)

(untitled) (Université TÉLUQ, 2025)
The purpose of this article is to build upon empirical research, leadership theory, open university practice, and shifting global trends to provide open university leaders with a framework for strategic reset. Strategic reset entails re-setting institutions’ priorities – making leadership choices – and taking action to build competitive advantage, quality, and service for the future. The foundational pillars of strategic reset are centred around 1) digitalization – specifically online capacity; 2) setting new strategic priorities, and 3) establishing a national footprint that aligns with critical national employment and workforce development needs. A secondary theme that weaves itself through this article is the need for open universities to revitalize their commitment to innovation. The article concludes by offering some tactical actions that open university leaders can consider for framing strategic reset and setting new priorities for the future. These include the following: 1) streamlined open university models; 2) precision access; 3) building a national service footprint; 4) renewal of critical partnerships; and 5) exploring alternative funding models.